2015
DOI: 10.1007/s11605-015-2830-3
|View full text |Cite
|
Sign up to set email alerts
|

Acute Mesenteric Ischemia Is a More Common Cause than Expected of Acute Abdomen in the Elderly

Abstract: AMI may be a more common cause of acute abdomen in elderly patients than is generally thought, emphasizing the importance of performing urgent computed tomography with contrast enhancement preferably in arterial and venous phases in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
68
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 110 publications
(75 citation statements)
references
References 18 publications
3
68
0
4
Order By: Relevance
“…However, the mean age of the patients, 64 years, was very low compared to the mean age of approximately 80 years in other studies that include unselected patients with AMI (due to arterial occlusive etiology) [1,4]. Thus, the patient population in the Arthurs' study does not represent the majority of AMI patients.…”
Section: Disregarding the Elderly In Patient Selection Is A Major Biamentioning
confidence: 82%
See 2 more Smart Citations
“…However, the mean age of the patients, 64 years, was very low compared to the mean age of approximately 80 years in other studies that include unselected patients with AMI (due to arterial occlusive etiology) [1,4]. Thus, the patient population in the Arthurs' study does not represent the majority of AMI patients.…”
Section: Disregarding the Elderly In Patient Selection Is A Major Biamentioning
confidence: 82%
“…Acute mesenteric ischemia is more common than expected in the elderly AMI due to arterial occlusive disease is generally considered a rare condition with hospital incidence rates ranging from 4.5 to 5.4 per 100,000 person-years [1][2][3]. On the other hand, it has been shown that AMI is 1.5 times more common abdominal emergency than ruptured abdominal aortic aneurysm [1,4]. Rare or not, AMI should never be overlooked as a possible cause of acute abdomen especially in the elderly.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…age 75 years, AMI is more common than acute appendicitis or ruptured abdominal aortic aneurysm [2]. While it is known that both timely diagnosis and rapid treatment are crucial for patient survival [3][4][5], there are no laboratory tests that would be diagnostic for AMI [6].…”
mentioning
confidence: 99%
“…The aims of this retrospective study were (1) to systematically assess the ability of radiologists to detect AMI in a CT of the acute abdomen performed in acute care setting, and (2) to identify factors associated with a missed or delayed diagnosis and patient outcome. For this purpose, we stratified the vascular and intestinal CT findings of AMI subdivided into the various etiologies, and analyzed whether the suspicion of AMI made by the referring physician had any impact on the correct CT diagnosis, and further, we studied which factors were associated with mortality and bowel resection rates.…”
mentioning
confidence: 99%